2002
DOI: 10.1074/jbc.m204006200
|View full text |Cite
|
Sign up to set email alerts
|

Gα and Gβγ Require Distinct Src-dependent Pathways to Activate Rap1 and Ras

Abstract: The Src tyrosine kinase is necessary for activation of extracellular signal-regulated kinases (ERKs) by the ␤-adrenergic receptor agonist, isoproterenol. In this study, we examined the role of Src in the stimulation of two small G proteins, Ras and Rap1, that have been implicated in isoproterenol's signaling to ERKs. We demonstrate that the activation of isoproterenol of both Rap1 and Ras requires Src. In HEK293 cells, isoproterenol activates Rap1, stimulates Rap1 association with B-Raf, and activates ERKs, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 78 publications
(100 reference statements)
8
40
0
Order By: Relevance
“…2E). These data demonstrate that Rap1 and ERKs can be activated by a PKA/SFK-dependent mechanism in PC12 cells, as has been shown for other cell types (Schmitt and Stork, 2002a).…”
Section: Regulation Of Endogenous Src By Pka In Pc12 Cellssupporting
confidence: 82%
See 1 more Smart Citation
“…2E). These data demonstrate that Rap1 and ERKs can be activated by a PKA/SFK-dependent mechanism in PC12 cells, as has been shown for other cell types (Schmitt and Stork, 2002a).…”
Section: Regulation Of Endogenous Src By Pka In Pc12 Cellssupporting
confidence: 82%
“…SrcS17A has been shown to selectively block the ability of Journal of Cell Science 117 (25) cAMP to activate Src in other cell types (Schmitt and Stork, 2002a). Cells were transfected with Flag-tagged wild-type Src or SrcS17A along with Flag-Rap1 and assayed for Rap1 activation following forskolin/IBMX treatment.…”
Section: Regulation Of Endogenous Src By Pka In Pc12 Cellsmentioning
confidence: 99%
“…Further studies have indicated that in many cell types, Ga s -mediated activation of ERK1/2 signaling via Rap-1 involves novel Rap-1-GEF known as Crk SH3 domain-binding guanine nucleotide-releasing factor, or C3G (Tanaka et al, 1994;Gotoh et al, 1995). It should be noted here that unlike the direct activation of EPAC by cAMP (de Rooij et al, 1998;Quilliam et al, 2002;Bos, 2006), the activation of C3G requires the PKA-mediated phosphorylation of Ser-17 of Src (Schmitt and Stork, 2002a;Obara et al, 2004;Weissman et al, 2002;Wang et al, 2006b), subsequent Src-mediated activation of Cbl, Cbl-mediated recruitment of Crk-C3G complex and Crk-SH3 domain-mediated recruitment as well as activation of C3G (Ichiba et al, 1999;Stork, 2000, 2002a). Results from these studies establish a paradigm in which Ga s stimulates ERK1/2 via a pathway involving cAMP-PKA-Src-mediated activation of C3G, C3G stimulation of Rap-1 and, finally, Rap-1-mediated activation of B-Raf-MEK-ERK module (Schmitt and Stork, 2000;Weissman et al, 2002;Obara et al, 2004;Wang et al, 2006b).…”
Section: Ga S Stimulation Of Erk1/2mentioning
confidence: 83%
“…Again, this process appears to involve a PKA-dependent phosphorylation of Src, or a Src-like kinase, leading to the activation of the small GTPase, Rap1, and subsequent repression of the RafRMKK1/2RERK cascade [214]. However, it is important to note that, in a different cell line, this signalling cascade can also be activated via PKA-dependent phosphorylation of Src [215]. Clearly, these data demonstrate the potential diversity of b 2 -adrenoceptor signalling and highlight the importance of characterising physiologically relevant responses under physiological conditions in nontransformed cells of the tissue of interest.…”
Section: Giembycz and R Newtonmentioning
confidence: 99%